HIV subtype is not associated with dementia among individuals with moderate and advanced immunosuppression in Kampala, Uganda - Sacktor, Ned (2014)
BACKGROUND: HIV-associated neurocognitive disorders (HAND) are a common neurological manifestation of HIV infection. A previous study suggested that HIV dementia may be more common among patients with subtype D virus than among those with subtype A virus among HIV+ individuals with advanced immunosuppression. We conducted a study to evaluate the frequency of HIV dementia, and the association of HIV dementia with HIV subtype and compartmentalization among HIV+ individuals with moderate and advanced immunosuppression (CD4 lymphocyte count >150 cells/μL and < 250 cells/μL). METHODS: The study enrolled 117 antiretroviral naïve HIV+ individuals in Kampala, Uganda. HIV+ individuals received neurological, neuropsychological testing, and functional assessments, and gag and gp41 regions were subtyped. Subjects were considered infected with a specific subtype if both regions analyzed were from the same subtype. RESULTS: 41% of the HIV+ individuals had HIV dementia (mean CD4 lymphocyte count= 233 cells/μL). 67 individuals had subtype A, 25 individuals had subtype D, 24 individuals were classified as A/D recombinants, and one individual had subtype C. There was no difference in the frequency of HIV dementia when stratified by HIV subtype A and D and no association with compartmentalization between the cerebrospinal fluid and peripheral blood. CONCLUSIONS: These results suggest that HIV dementia is common in HIV+ individuals in Uganda. There was no association between HIV subtype and dementia among HIV+ individuals with moderate and advanced immunosuppression. Future studies should be performed to confirm these results.